Studi Kelayakan Aplikasi Kubuku E-Resources Berdasarkan Model Analisis PIECES Pada Perpustakaan Digital APMD Yogyakarta - Ramadhani Ginting (Media Pustakawan, 2020)
This research is a feasibility study in the APMD Digital library using the Kubuku E-Resources application based on the PIECES framework analysis model outlined in 6 focus analysis of Performance, Information, Economy, Control, Eficiency and Service. PIECES framework can be used to determine the pros and cons of the application, so that it can serve as a reference in decision making to subscribe to the application in the following year or vice versa. In this study used quantitative descriptive methods. Data is obtained using questionnaires and data analysis using Likert scales. The results showed that the average value of the feasibility level of the APMD library to subscribe to the Kubuku E-Resources application as a Digital library reached 3.73 or with a decent predicate.